The phenomenon of literal association in the Qur’ān - Almuways, Yasir Sulaiman Abdurahman; Elatrash, Radwan Jamal Yousef (IIUM Press, International Islamic University Malaysia, 2020)
This article highlights the phenomenon of the Literal Association (Ẓāhiratal-Mushtarak al-Lafẓī)within the science of Tafsīrand Qur’ānin which the perspectives of some of the scholars of Tafsīrwill be viewed, analysed, and evaluated in order to get to the conclusion of whether or not such a linguistic phenomenon exists in the Qur’ānby providing some examples from the Qur’ānand the comments of the scholars of Tafsīron those examples. My theory of research is based on the analytical research methodology and inductive research methodology, which will employ both the quantitative and qualitative approaches by which we explore the definition of the literal association in the Qur’ān, the types of literal association in the Qur’ān, the opinions and the disputes of the scholars of Tafsīr(interpretation) about the existence of literal association in the Qur’ān, and some examples from the Qur’ānillustratingthe existence of literal association in the Qur’ān.